PENGENDALIAN KUALITAS PRODUKSI UNIT PLATE HEAT EXCHANGER (PHE) PADA PROSES WELDING KONEKSI DENGAN PENDEKATAN PDCA UNTUK MENINGKATKAN PERFORMANSI CYCLE TIME - Arif Widiantoro; Muhammad Hermansyah (Department of Industrial Engineering - Universitas Yudharta Pasuruan)
Global business and industry competition in the field of heat exchangers is a threat to all companies, especially in terms of product manufacturing cycle time in this study, it is known that the problem is the average length of welding process of the connection process of the Plate Heat Exchanger (PHE) unit which takes 3.45 hours each time the process so in this study aims to determine the increase in cycle time in the connection welding process in the existing PHE unit assembly process, the method used to increase the cycle time of the connection welding process is to use the Plan, Do, Check, and Action (PDCA) method, The application of this method has 4 stages: a Plan to identify existing problems and their root causes, Do is a step to carry out all improvements directed at the root of the problem, Check is a stage for the process of checking the comparison of data before and after the repair process based on the results of improvement there and Acti on is an action after repairs and the results are known, namely the implementation of standardization of processes that aim to guarantee the results and certainty of the next process. The results of this study are improvements that all welding connection processes using manual methods have been replaced by making simple machines so that the process can be more stable , consistent and efficient, the results of improvements that have been made can increase the cycle time of the connection welding process which was originally 3.45 hours to 0.97 hours per process.